2008
DOI: 10.1111/j.1442-2050.2000.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Late esophageal toxicity using a combination of external beam radiation, intraluminal brachytherapy and 5-fluorouracil infusion in carcinoma of the esophagus

Abstract: One hundred patients with potentially curable squamous cell carcinoma of the esophagus were treated using a combination of external beam radiation, medium-dose intraluminal brachytherapy (ILBT), and 5-¯uorouracil infusion (as a radiosensitizer) from January 1990 to December 1993. The main objective was to determine late toxicity and optimization of the dose of intraluminal radiation. All patients had external radiation of 50 Gy over 5 weeks, followed by ILBT of 20 Gy for 50 patients (group 1) and 15 Gy for a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Notably, the patients in this study were administered chemotherapy just prior to ILRT. [19] Significantly fewer incidences of strictures was seen when ILRT dose was reduced from 20 to 15 Gy (24% vs 8%). The retrospective report on factors affecting the development of strictures following treatment of esophageal carcinoma also found highest complication rates among patients receiving concurrent chemoradiotherapy followed by brachytherapy.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Notably, the patients in this study were administered chemotherapy just prior to ILRT. [19] Significantly fewer incidences of strictures was seen when ILRT dose was reduced from 20 to 15 Gy (24% vs 8%). The retrospective report on factors affecting the development of strictures following treatment of esophageal carcinoma also found highest complication rates among patients receiving concurrent chemoradiotherapy followed by brachytherapy.…”
Section: Discussionmentioning
confidence: 87%
“…Complications following the use of ILRT with chemoradiotherapy have been varyingly reported by different investigators. While Montravadi et al, [4] reported no patient developing fistula post treatment, Sharma et al, [19] on the other hand reported a 12% incidence of fistula formation and 29% incidence of post-treatment esophageal ulcers. Notably, the patients in this study were administered chemotherapy just prior to ILRT.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial has already demonstrated that combined therapy is superior to EBRT alone, but whether EBRT adds anything to brachytherapy has not yet been established 13 . Adding chemotherapy to brachytherapy or EBRT in patients with poor performance status, low BMI, and significant comorbidities, has been shown to increase toxicities, including local esophageal scarring and fistulae that can make dysphagia worse 14,15 . However, subsequent to local therapy to the esophagus that palliates dysphagia, patients can improve eating, weight and performance status.…”
Section: Discussionmentioning
confidence: 99%